An??lise da ??rea de treinamento empresarial pela ??tica de ganho ou perda dos recursos aplicados - Alves, Ricardo (2003)
training area of companies considering the gain or loss aspects of the resources so applied. The main results refer to the need of companies to invest in personnel training while, at the same time, there is substantial loss of the resources so applied due to discontinuities, to immediateness and to business fads. Another important finding regarding companies is that there is no clear differentiation among the concepts of training, development and corporate education. Such indefiniteness leads to questioning the feasibility of applying financial resources on these activities. As a final conclusion, it is noticeable that the results of this work, taking into account the limitations of the methodology applied, indicated that the risk of the training efforts turning into losses is greater than that of becoming gains.